(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The Satanic Verses by Salmon Rushdie is a fictional novel that incorporates the use of magical realism to a large extent (Albertazzi 28). The story depicted in the book was inspired by the life of the Islamic Prophet, Mohammed in part. Several Quran teachings are also portrayed. For instance, the title of the book is derived from three pagan goddesses whose story is told in the Quran. The narration of the story is also crafted in line with contemporary events concerning immigration. This paper looks into the controversies surrounding the novel.